Transformasi Digital Sistem Kehadiran untuk Budaya Hybrid Work dengan TOGAF Framework - Mareta, Arvin; Yohannis, Alfa (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
Since the end of the COVID-19 pandemic in 2023, hybrid work or work from anywhere (WFA) methods have become increasingly popular. While this work culture offers flexibility, it also poses challenges for companies in monitoring employee attendance. This study proposes the implementation of the TOGAF Framework to design an attendance management system that supports a hybrid work culture. The design process begins with a preliminary phase to identify user needs and the limitations of traditional systems. The system is designed using TOGAF ADM (Architecture Development Method), covering phases such as Architecture Vision, Business Architecture, Information System Architecture, and Technology Architecture. Technologies such as IoT, GPS, facial recognition, and mobile applications are employed to ensure system flexibility and accuracy. Testing is conducted in two stages: Blackbox Testing to verify functionality against specifications, and User Acceptance Testing (UAT) to evaluate system usability in real-world conditions. The test results show that the system meets all specifications, improves operational efficiency by up to 40%, and ensures the security and accuracy of attendance data. The system is also designed for integration with other modules, such as payroll and HRIS, to support strategic decision-making. This approach provides an effective and adaptive solution for monitoring employee attendance, whether working remotely or in the office, and enhances productivity in modern work environments.